COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE IN ASIA CENTRAL BANK (BCA) WITH INDONESIAN PEOPLE BANKS (BRI) LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) IN 2019-2021 - Yuni Srianingsih; Muhammad Fauzan; Ahmad Rifai (Indragiri Research Center (ingreat), 2023)
This study aims to obtain descriptions of ROA, LDR and CAR at Bank BCA and Bank BRI and to analyze the differences in ROA, LDR and CAR at Bank BCA and Bank BRI which are listed on the Indonesia Stock Exchange (IDX) for 2019-2021. the variables in this study are ROA, LDR and CAR. The population of this study are BCA Banks and BRI Banks which are registered on the IDX in the 2019-2021 period. The sampling method used is a saturated sample (all populations are sampled) Bank BCA and Bank BRI in 2019-2021 with computer aids that use the SPSS program. 23 for windows. Analysis of the financial statements in the form of these ratios includes the first liquidity ratio, this ratio shows aspects of the company's ability to meet obligations that are due in the short term. ROA, LDR and CAR are aspects that can be used to measure the performance of a company. This research was carried out using a comparative approach, a comparative research approach is a comparative research, which is carried out to compare the similarities and differences of 2 or more characteristics and facts of the object under study based on a certain frame of mind. The type of data in this study is quantitative data in the form of financial report figures at Bank BCA and Bank BRI. The data analysis technique used in this research is comparative analysis, which is a technique using the independent sample T-test. From the results of research that has been done to look at the financial performance of Bank BCA and Bank BRI with CAR ratios there is no difference in the financial performance of the two banks, while there are differences in the ROA and LDR ratios. By conducting independent differential tests the T-test samples on ROA and LDR values ​​can be used as benchmarks to measure the financial performance of the two banks.